Ethnic stereotypes and prejudices of modern Russian youth - V. V. Levchenko; T. Yu. Pavlenina (Вестник университета)
The article examines the theoretical foundations of the analysis of ethnic stereotypes and prejudices that have developed in modern sociological and socio-psychological science. The patterns of this phenomenon characteristic of modern society are highlighted. The results of the authors’ own empirical study of ethnic stereotypes and prejudices of modern Russian youth are presented that made it possible to identify the regional specificity of the manifestation of this phenomenon among Perm youth and to compared it with the Moscow youth. The specificity was identified according to behavioural (behaviour in the process of interethnic conflict; existence of interpersonal relationships with representatives of another ethnic group; orientation towards a certain type of relationship with representatives of another ethnic group), cognitive (knowledge about representatives of their own and other ethnic groups; trust in services provided by representatives of different ethnic groups and by migrants; trust in representatives of different ethnic groups) and emotional parameters (emotional attitude to the culture and traditions of another ethnic group; emotional attitude to interethnic conflict). The main factors influencing the formation of ethnic stereotypes and prejudices among Perm and Moscow youth are clarified. These results can be used for further study of regional characteristics of interethnic relations and ethnic stereotypes, prejudices, their dynamics and effective interaction of ethnophors as well as to optimise the process of interethnic relations.